Challenges of mental health nursing in family health strategies (Research, Society and Development, 2020)
The aim of the present study was to investigate the challenges of nursing care within the scope of Mental Health in the Family Health Strategies. This is a cross-sectional, mixed, quantitative and qualitative research, in which 24 participants were interviewed, 4 nurses and 16 nursing technicians, in 8 ESF teams in the city of Maceió - AL, randomly classified during the program Excel®. Among the results found, we highlight the lack of practices in Mental Health, lack of capacity and inadequate infrastructure, inadequate human and monetary resources, cultural predominance for ineffective assistance, ideology of treatment in Mental Health is for crazy people and not as a disease to be treated , reception and safety of the nursing team. It was concluded that the challenges, despite recidivists, are particular among those that occurred as a result of their knowledge, precepts and experiences. The participants identified their challenges, anxieties, needs and, consequently, achieved reflexes about actions and practices that can be performed in the SM, or that allow changes in assistance.